Plasma-Assisted Chemical Vapor Deposition of TiBN Coatings on Nanostructured Cemented WC-Co - Matija Sakoman; Danko Ćorić; Mateja Šnajdar Musa (Metals, 2020)
The plasma-assisted chemical vapor deposition (PACVD) technique has shown many advantages in applications, where thin coatings with superior wear properties are demanded, especially for geometrically complex parts. In this study, multilayered gradient TiBN coatings that were deposited on nanostructured cemented carbides by the PACVD method were investigated. Nanostructured samples of cemented carbides with the addition of 5 and 15 wt.% Co were sintered by the hot isostatic pressing, sinter-HIP technique. Surface preparation was conducted on samples in order to enable maximum coating adhesion. Tests that were conducted on produced samples aimed to investigate the mechanical and physical properties of coated samples. These tests included nanoindentation, surface layer characterization, and coating adhesion evaluation while using the Rockwell and scratch test. The obtained results confirmed that the PACVD process can be utilized for applying thin hard coatings to nanostructured cemented carbides that are produced by the sinter HIP process, resulting in a base material/ coating system that exhibits excellent physical and mechanical properties. The results presented in this paper give a valuable contribution to the research of TiBN coating systems and their potential for application under heavy wear conditions.